2018
DOI: 10.7163/sow.49.6
|View full text |Cite
|
Sign up to set email alerts
|

Rola wyróżników krajobrazu wiejskiego w procesie rewitalizacji wsi = The role of rural landscape distinguishing features in the process of rural revitalization

Abstract: Przeobrażenia zachodzące na terenach wiejskich spowodowane są różnorodnymi czynnikami natury wewnętrznej (wynikającymi wprost z uwarunkowań konkretnego obszaru) lub zewnętrznej (niezależnych od analizowanego terenu). Wywołują one silne zmiany krajobrazu wiejskiego, w tym jego podstawowego elementu, jakim jest wieś. Zróżnicowane skutki przemian widoczne są w wizerunku miejscowości i niestety, najczęściej mają one negatywny charakter. W efekcie obserwuje się zatarcie tradycji miejsca, odrębności i specyfiki regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 0 publications
0
8
0
1
Order By: Relevance
“…It is worth noting that the results of the survey on the preferences of visitors staying in holiday villages showed that respondents when choosing a village gave priority to its traditional character [9][10][11][12][13]64,67,69]. Research into agritourism also indicated that its development is influenced both by the so-called natural attractiveness factor (natural and landscape values) and cultural attractiveness (historical monuments, regional buildings) [7,9,60]. Therefore, it was considered that the area of Kłodzko District would be optimal for examining many indicators in terms of favoring agritourism as one of the economic sectors (tourism).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is worth noting that the results of the survey on the preferences of visitors staying in holiday villages showed that respondents when choosing a village gave priority to its traditional character [9][10][11][12][13]64,67,69]. Research into agritourism also indicated that its development is influenced both by the so-called natural attractiveness factor (natural and landscape values) and cultural attractiveness (historical monuments, regional buildings) [7,9,60]. Therefore, it was considered that the area of Kłodzko District would be optimal for examining many indicators in terms of favoring agritourism as one of the economic sectors (tourism).…”
Section: Resultsmentioning
confidence: 99%
“…In the first category-the homogeneity of the regional style-the following features were distinguished: the color and form of the roof (roof slope inclination) and the body and covering of the building façade. These are the features that are most visible when observing buildings on a landscape scale [7][8][9]58,59]. The second category-the quality of the panoramas-determines the location of the farm in space: whether the site is in a prominent place in the field or whether it is located in the vicinity of similar buildings [41,[43][44][45]49,50].…”
Section: Assessment Categories For Agritourism Farmsmentioning
confidence: 99%
See 1 more Smart Citation
“…Manor and park estates are valuable elements of the cultural heritage and a distinguishing feature of the rural landscape in Western Pomerania [60,66]. However, they have often been subject to changes since 1945, including alterations to their functions, inappropriate renovations, and decades of neglect.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research focusing on the current status of manor houses and parks in rural areas of Western Pomerania has been lacking. However, valuable comparative information can be obtained from research conducted on northern and western Poland, which also belonged to Germany before the war, for instance on East Prussia [61], Silesia [62][63][64], Lower Silesia [65,66], and Warmia-Masuria [7,67,68]. The research mainly discussed the historical structure of the sites, whereas Łaguna [7,68] attempted to develop a method for assessing the status of villages managed by state institutions.…”
Section: Introductionmentioning
confidence: 99%